Association between the behavior of eating disordered and sleep disturbance in Shahid Beheshti University of Medical Students - Golmohammadi, Maryam; Samieefar, Noosha; Yari Boroujeni, Reza; Rezazadeh, Arezoo (Social Determinants of Health, 2019)
Background: Recent studies have shown that sleep difficulties could be related to abnormal eating patterns. Apparently, eating and sleeping behaviors both affect human lives. Dysregulation of these behaviors lead to distress and negative health and psychological outcomes. The present study aimed to investigate the association between disordered eating behaviors and sleep disturbance among medical students. Methods: This was a cross-sectional study which was conducted at Shahid Beheshti University of medical sciences. The eating disorder behaviors were assessed based on the Eating Attitudes Test-40 questionnaire and Sleep disturbances were assessed by two items related to difficulties initiating sleep (DIS) and maintaining sleep (DMS). Each individual correlation was used to calculate variable associations. Linear multiple regression analysis was performed to identify variables contributing to an explanation of sleep difficulties. Results: In total, 172 people participated in this study. It was observed that bulimic behaviors (BB) and social pressure to eat (SPE) were the dimensions that significantly explained difficulties maintaining sleep (r=0.207, P<0.001 and r=0.286, P<0.001, respectively) and overall sleep disturbances (r=0.355, P=0.001 and r=0.225, P=0.003, respectively). Negative correlation between body mass index (BMI) and difficulties maintaining sleep (DMS) (r=-0.069, P=0.527) was not remarked which was found in males. Conclusion: It was ultimately attained that age and sex could be accounted as confounder variables in the association between sleep disturbance and eating behaviors. The results indicated that a normal eating behavior has a positive relation with the quality of sleep.